The role of diet and nutritional deficiences in neurodegenerative diseases - Wąsik, Joanna; Kurkiewicz, Wojciech; Woźniak, Oskar; Mikulska, Jowita; Gryboś, Kacper; Lewandowski, Mikołaj; Sepioło, Weronika; Kiełbratowska, Julia; Kwiatkowska, Zofia (Quality in Sport, 2025)
Purpose of reaserch: This is a review of the literature on the most common neurodegenerative diseases, their causes, impact on physical and mental health, diets and nutritional deficiencies influencing the development or course of the disease.Materials and methods: The literature review was based on materials retrieved from the PubMed and Google Scholar databases, using keywords such as ,,neurodegenerative disease’’, ,,Diet In Alzhaimer disease’’, ,,Diet In Parkinson disease’’. The scope of the studies analyzed covered the years 1999 to 2024, with a focus on recent research.Results: Neurodegenerative diseases are incurable, and a factor relatively as easily modifiable as an adequate diet influences both the onset and course of the disease. An appropriate diet can delay the onset of some symptoms as well as alleviate them, but much research is still needed to determine which diets have a protective effect and which diets or products will increase symptoms.Conclusions: Neurodegenerative diseases are increasingly common in ageing societies, more and more patients will face these diseases. This is why it is so important to protect the patient in every possible way, to prevent or reduce their ailments, and proper nutrition is a relatively easily modifiable factor that can aid this process. We compared the work of dozens of authors from different corners of the world who studied the effects of different products and diets on the development of neurodegenerative diseases.